Endogenous Transportation Technology in a Cournot Differential Game with Intraindustry Trade - Luca Colombo; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
We investigate a dynamic Cournot duopoly with intraindustry trade, where firms invest in R&D to reduce the level of iceberg transportation costs. We adopt both open-loop and closed-loop equilibrium concepts, showing that a unique (saddle point) steady state exists in both cases. In the open-loop model, optimal investments and the resulting efficiency of transportation technology are independent of the relative size of the two countries. On the contrary, in the closed-loop case, a home market effect operates so that the firm located in the larger country invests more than the rival located in the smaller one. Policy implications are also evaluated.
Keywords: 330